Análisis de la evolución de la cultura tributaria en el Ecuador y su incidencia en la elusión del impuesto a la renta en las personas naturales no obligadas a llevar contabilidad, habitantes en el sector norte de Guayaquil en la Parroquia Tarqui - Arévalo Águila, Deniss Ivette (2015)
This research will serve us to understand what has been the evolution of the tax culture in Ecuador, in the natural people of the Tarqui parish of Guayaquil city. Through statistical tool like the Survey, Crosstabs, Correlation Analysis, Contingency Analysis will allow us to know the tendency of the taxpayer regarding their tax culture and this tendency is toward tax avoidance. We analyzed books, writings, economic reports, bulletin of the Central Bank, Statistical Reports published by the Internal Revenue Service and other works in order to know in detail in the legal framework governing or protects natural persons in Ecuador, also was accessed material on the historical tax development, which helped to reinforce the criterion on evolution Surveys through questions in Likert scales allowed to know the tendency of the taxpayer on tax matters, were conducted comparative between different variables to know its tendency and with the help of the tool Contingency Analysis could analyze the association between two or more variable, resulting information relevant to this investigation. The sample taken from the Tarqui parish, is 384 taxpayers inhabitants of the Tarqui parish of Guayaquil city, about their perception of the tax culture, about their feelings regarding their obligations and willingness to comply with them.